x-3/2-7=x-8/3

Simple and best practice solution for x-3/2-7=x-8/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3/2-7=x-8/3 equation:



x-3/2-7=x-8/3
We move all terms to the left:
x-3/2-7-(x-8/3)=0
We add all the numbers together, and all the variables
x-(+x-8/3)-7-3/2=0
We get rid of parentheses
x-x-7+8/3-3/2=0
We calculate fractions
There is no solution for this equation

See similar equations:

| 5x-99x-218=0 | | 0.005(x+3)=0.006+0.013 | | 4x/7-7/8=19/56 | | 3a+5=2a+20 | | 7x/9-8=48 | | 2(x+2)–3(5–x)=x+5(x–3) | | 5.8/x-62=4 | | 9(z+1)-2(z-3)=3(z-4)+3(z-3) | | 0.75x+0.05(6-x)=0.10(45) | | 9x^2−35x+4=8 | | x-7/2-1=x-4/3 | | 2/f=5-2f | | -45x–13=77+90 | | ((4x-9)(4x-9))+25=0 | | -0.10(29)+0.35x=0.05(x-10) | | 61=-7x | | X/x-3-6/x^2-2x-3=1 | | 0.11y+0.05(y+5000)=1370 | | U/3+2=u/4 | | 6x/7-1=5 | | (m+4)(m+1)=0 | | 6t+1/5=t+8/10+t-6/10 | | 8/4x-8-6/3x-6=0 | | 6z+5z=20-12 | | x–(27)=35–12 | | 5x−3=4x+5 | | 3(2z-4)=-5(z+4) | | 6x+7/4x-1=-3x-8/4-2x | | 3x+12/4+x+16/6=13 | | 2x^​2​​−2x−180=0 | | 8x-7×-3=-3 | | 21x-20x=17+3 |

Equations solver categories